Determination of weight conversion factors for some Philippine fish - Gonzales, Lourdes Taracatac; Florencio, Cecilia A. (1976)
Weight conversion factors for cooked and raw fish were determined. Twenty-seven species of small, medium, large and cross section slices of fresh and processed fish were studied. Five trials contributing five observations for each species of fish for boiled and fried samples were performed. Conversion factors were computed from the ratio of the raw and cooked weights of the whole fish as well as of the head, middle and tail portions of large fish. The amount of cooking oil absorbed by the edible portion of fried fish was also calculated. Generally, fish lose weight upon cooking, except boiled dried fish where an increase in weight was observed. There was a greater weight decrease in fried than boiled samples. Statistical analysis of conversion factors derived revealed no significant differences between trials within a species of fish. However, with but a few exceptions, differences in conversion factors between species were found significant. In order to minimize either underestimation or overestimation of the true weight of fish, the use of individual conversion factors for some species of fish is necessary.
Appendices: leaves 84-135.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Quezon City.
Keywords: Fishes -- Philippines -- Weight and measurement